2018
DOI: 10.2176/nmc.oa.2018-0148
|View full text |Cite
|
Sign up to set email alerts
|

Flow Diverter Therapy Using a Pipeline Embolization Device for 100 Unruptured Large and Giant Internal Carotid Artery Aneurysms in a Single Center in a Japanese Population

Abstract: Flow diverters (FDs) have been developed for intracranial aneurysms difficult to treat with conventional endovascular therapy and surgical clipping. We reviewed 94 patients with 100 large or giant unruptured internal carotid artery (ICA) aneurysms treated with Pipeline embolization device (PED) embolization from December 2012 to June 2017 at Juntendo University Hospital. The patients’ mean age was 63.4 years (range, 19–88), and there were 90 women 89.4%. Aneurysm locations were: C4 (45), C3 (4), and C2 (51) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 37 publications
0
40
1
1
Order By: Relevance
“…Case 2 with carotid cavernous fistula caused by delayed aneurysm rupture was treated by transvenous aneurysmal embolization (Figure 2). 4,34 Only one case (Case 3) of the anticoagulant group with additional coiling did not suffer postoperative delayed aneurysm rupture, and achieved complete obliteration at the final follow up. Flow diverter placement with additional coiling or parent artery occlusion if tolerated will be effective for the prevention of aneurysm rupture and minimize complications.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Case 2 with carotid cavernous fistula caused by delayed aneurysm rupture was treated by transvenous aneurysmal embolization (Figure 2). 4,34 Only one case (Case 3) of the anticoagulant group with additional coiling did not suffer postoperative delayed aneurysm rupture, and achieved complete obliteration at the final follow up. Flow diverter placement with additional coiling or parent artery occlusion if tolerated will be effective for the prevention of aneurysm rupture and minimize complications.…”
Section: Discussionmentioning
confidence: 92%
“…The flow diverter is a new device for the endovascular treatment of cerebral aneurysms which are otherwise difficult to treat. [1][2][3][4][5] The effectiveness of the flow diverter is now established, but the high metal coverage ratio may cause ischemic complications such as perforator occlusion or thromboembolism. 6,7 Prevention of these ischemic complications during endovascular surgery requires preoperative administration of antiplatelet agents.…”
Section: Introductionmentioning
confidence: 99%
“…Oishi et al reported two delayed aneurysm rupture, but all developed carotid cavernous fistulas. They put adjunctive coils when the aneurysm was expected with a high risk of delayed rupture, which was located in the subarachnoid space with the jet flow with a narrow neck, irregular shape, and more than 15 mm [22]. However, as previously mentioned, additional coil insertion with FD is not allowed in our country.…”
Section: Discussionmentioning
confidence: 96%
“…In a large Japanese series of FD for large and giant UIAs, complete occlusion was achieved in 63 out of 91 aneurysms (69.2%). They used multiple overlapping or telescoping FDs in 23 patients and inserted additional detachable coils in 34 aneurysms (34%) [22]. Although FD had a higher complete or near-complete occlusion rate than coil embolization, complication and mortality rates were not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, angiographic complete occlusion rate, residual neck, and residual aneurysms were found to be 76.0%, 7.5%, and 5.7%, respectively, at 6 months followup, whereas the same rates were found to be 93.4%, 2.6%, and 2.6%, respectively, at 3 years follow-up [1]. Oishi et al [19] found that complete occlusion rate, residual neck, and residual aneurysms were found to be 69.2%, 19.2%, and 9.6%, respectively, at one year follow-up in 52 of 100 large and giant unruptured aneurysms treated with PED.…”
Section: Discussionmentioning
confidence: 84%